Islamic Society in the Digital Era: The Role of Celebgrams in the Development of Generation Z in Lampung - Faizal Faizal; Imanudin Imanudin (Departement of Mathematics Education, 2025)
Abstract The purpose of the research is to analyze and understand the role of Muslim celebrities/influencers in Lampung in shaping Islamic values in society for generation Z, promoting Islamic preaching through social media , contributing to the development of Islamic society amidst the challenges of globalization for generation Z. The research method uses qualitative with a phenomenological research type. The research location is in Bandar Lampung City. The research subjects are famous Muslim celebrities or influencers who live or have influence in the Lampung area, especially Bandar Lampung City, totaling 1 person. Data collection techniques are semi-structured interviews and non-participant observation. Data analysis includes several stages, namely data reduction (the process of determining, cutting attention, and simplifying data carried out by making an outline of the data that researchers obtain from the field); data presentation (in the form of descriptions or narrative texts); drawing conclusions (concluding that the given conclusions are temporary and can be changed if the supporting evidence is strong). The results of the study indicate that Muslim celebrities in Lampung, especially Els Warouw, play a significant role in shaping Islamic values among the younger generation. The use of social media as a platform for preaching allows celebrities to reach a wider audience in a creative and interactive way. Through interesting content such as educational videos, halal lifestyle inspiration, and motivational messages, celebrities have succeeded in encouraging active audience participation in religious discussions.